2019
DOI: 10.1186/s12877-019-1272-2
|View full text |Cite
|
Sign up to set email alerts
|

Health systems readiness to provide geriatric friendly care services in Uganda: a cross-sectional study

Abstract: Background As ageing emerges as the next public health threat in Africa, there is a paucity of information on how prepared its health systems are to provide geriatric friendly care services. In this study, we explored the readiness of Uganda’s public health system to offer geriatric friendly care services in Southern Central Uganda. Methods Four districts with the highest proportion of old persons in Southern Central Uganda were purp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 25 publications
4
34
0
Order By: Relevance
“…For the most part, tools to assess ‘readiness’ for uptake of specific policies or scale-up of existing interventions in LMIC involve mapping essential resources, knowledge and skills needed to implement a new intervention or initiative at facility-level ( WHO 2015 ). While useful in ranking facilities according to their capacity, in principle, to provide basic health services at minimum standards ( Jigjidsuren et al , 2019 ; Ssensamba et al , 2019 ), these tools lack consideration of the software dimensions of ‘readiness’ related to individual and collective agency to implement change.…”
Section: Discussionmentioning
confidence: 99%
“…For the most part, tools to assess ‘readiness’ for uptake of specific policies or scale-up of existing interventions in LMIC involve mapping essential resources, knowledge and skills needed to implement a new intervention or initiative at facility-level ( WHO 2015 ). While useful in ranking facilities according to their capacity, in principle, to provide basic health services at minimum standards ( Jigjidsuren et al , 2019 ; Ssensamba et al , 2019 ), these tools lack consideration of the software dimensions of ‘readiness’ related to individual and collective agency to implement change.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the surge in numbers of elderly people and the increase in the burden of chronic diseases among the aged, a recent study by Dotchin et al, revealed that, there are few geriatricians in Africa, due to no formal undergraduate/ postgraduate training for medical students in geriatrics [7]. In Uganda, a study by Ssensamba et al, showed a low preparedness of public health facilities to offer geriatric cordial care services due to gaps in the healthcare systems, thereby calling for healthcare reforms to sufficiently cater for service provision for the aged in Uganda [8].…”
Section: Discussionmentioning
confidence: 99%
“…As for other types of health care provision, there are three articles on primary care [49][50][51], one on tertiary care [52], and seven articles that address care integration [53][54][55][56][57][58][59]. It is understood that care integration concerns the promotion of integrated and continuous health care processes in space and time [60].…”
Section: Nature Of Carementioning
confidence: 99%
“…In this sense, there was a prevalence of a set of four fields related to the concept of Age-Friendly Hospital-Management policy, Communication, and services, Care processes and Physical Environment-and a set of fields concerning the "Age-Friendly Emergency Department"-Social climate, Policies and procedures, Systems and processes of care, and Physical environment (See Table 1). The most common WHO Principle to these studies (with the exception of [58]) was the "Physical environment", which required the attention of all authors in an exclusive or complementary manner with regard to the application of the guidelines of universal design.…”
Section: Fields Of Actionmentioning
confidence: 99%
See 1 more Smart Citation